Communication in the Spaceflight Multi-Team System: Training and Technology Recommendations to Support Boundary Spanners. (September 2017) - Anania, Emily C.; Disher, Timothy J.; Kring, Jason P.; Iwig, Chelsea L.; Keebler, Joseph R.; Lazarra, Elizabeth H.; Salas, Eduardo
Long-duration exploration missions (LDEMs) in space rely on the coordinated efforts of a large, dynamic, and global multi-team system (MTS) that crosses organizational, geographic, cultural, and temporal boundaries. A key role in the spaceflight MTS is the leader who connects or spans the boundaries between distinct teams and supports the development of team cognition. The purpose of the present paper is to provide recommendations on how to train "boundary spanner" leaders and the tools they use to coordinate and communicate with teams in the context of a LDEM MTS. To this end, we address four specific questions focused on 1) how the MTS will change for future missions, 2) identifying the primary boundary spanners, 3) identifying the key attitudes, behaviors, and cognitions (ABCs) for effective boundary spanners, and 4) communication technologies to support the development of team cognition in the MTS. Results indicate six critical boundary spanner roles in the NASA Mission Control Center and 12 ABCs that should be trained. We conclude with concrete recommendations for NASA and its partners to empirically test different training approaches and commercial task management tools the MTS can use to improve communication efficiency and accuracy.